Using bacteriophages to assure food safety: A natural and effective tool to combat foodborne pathogens - Ummad Tariq (BioScientist: The Salford Biomedicine Society Magazine, 2024)
Food safety is a major concern around the world, with millions of people suffering from foodborne illnesses each year. Traditional techniques of ensuring food safety, such as pasteurisation and chemical preservatives, have limitations, prompting the search for new solutions. Bacteriophages, which are viruses that particularly target and kill bacteria, represent a possible alternative. This article investigates the use of bacteriophages to improve food safety by describing their mechanisms of action, uses in different food industries, benefits over old approaches, and obstacles. Bacteriophages are very selective to harmful bacteria, minimising contamination while neither hurting beneficial microbiota nor modifying food characteristics. ListShield™, a phage preparation, can efficiently decrease pathogens including Listeria, Salmonella, and E. coli in meat, poultry, fresh vegetables, dairy products, and seafood. While bacteriophages provide a novel and natural alternative, regulatory constraints, potential bacterial resistance, and public image all pose barriers to their widespread implementation. Continued research and education are critical for overcoming these limitations and using bacteriophages to improve global food safety.